Diagnosis of severe fever with thrombocytopenia syndrome (SFTS) in a cat with clinical findings resembling lymphoma - IRIE, Mitsuhiro; MIYOSHI, Takuma; HIRAMOTO, Akira; HIRATA, Masahiko; TAKANOSU, Masamine; PARK, Eun-Sil; MAEDA, Ken (Journal of Veterinary Medical Science, 2022)
A two-year-old male domestic cat showed lethargy, tonic-clonic convulsion, and mucosal jaundice. Upon admission, blood examination indicated severe neutropenia and thrombocytopenia, and ultrasonography revealed diffuse splenomegaly with a honeycomb appearance and abdominal lymph nodes enlargement in addition to a decrease in cardiac blood flow indicating a shock condition. Cytology of the spleen showed a cell population composed of immature large lymphoid cells with distinct nucleoli, suggesting lymphoma. The cat received symptomatic treatments but died four hours later. Reverse transcriptase polymerase chain reaction assay of the spleen sample indicated the presence of severe fever with thrombocytopenia syndrome (SFTS) virus S gene segment. Clinical features of this case that was diagnose as SFTS were similar to lymphoma. Therefore, pet owners and veterinary workers should be protected against infection of SFTS.